f(x)=x(x-1)(x-2)(x-3)(x-4) f'(1)=?求详解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 03:32:47
f(x)=x(x-1)(x-2)(x-3)(x-4)f''(1)=?求详解f(x)=x(x-1)(x-2)(x-3)(x-4)f''(1)=?求详解f(x)=x(x-1)(x-2)(x-3)(x-4)f''
f(x)=x(x-1)(x-2)(x-3)(x-4) f'(1)=?求详解
f(x)=x(x-1)(x-2)(x-3)(x-4) f'(1)=?
求详解
f(x)=x(x-1)(x-2)(x-3)(x-4) f'(1)=?求详解
f'(1)=lim(x->1)[f(x)-f(1)]/(x-1)
=lim(x->1)[x(x-1)(x-2)(x-3)(x-4)]/(x-1)
=lim(x->1)[x(x-2)(x-3)(x-4)]
=1×(-1)×(-2)×(-3)
=-6
f'(1)=lim(x->1)[f(x)-f(1)]/(x-1)
=lim(x->1)[x(x-1)(x-2)(x-3)(x-4)]/(x-1)
=lim(x->1)[x(x-2)(x-3)(x-4)]
=1×(-1)×(-2)×(-3)
=-6
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)
F(X)满足F(x)+2f(x分之1)=3X,求f(x)
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)?
已知f(x)满足2f(x)+f(-x)=-3x+1,求f(x)
已知f(x)满足f(x)+2f(1/x)=3x,求f(x) ,
f(x-1)=x^2-2x+3(x
f(x)=(x-1)(x-2).(x-3)求导
f(x)=5x+3 f(x)=5x f(x)=x+2x+1 f(x)=5x+3 f(x)=5x f(x)=x+2x+1
F(x)=3x^2+2x-1 求F(x+△x)-f(x)/ △x
已知函数f(x)=x^3+x^2-2x-x,f(1)f(2)
设f(x)={3x-1,x=0,求f(-x),f(x-2).
f(x+1)+f(x-1)=4x^3-2x求f(x)
已知f(x+1/x-1)=3f(x)-2x,求f(x)
已知f(x)+2f(1/x)=x+2/x+3,求f(x)
f(x)=x^2+x (x
f(x)={2x+1,x
f(x)={1+x/2,x
f(x)=(x-1)/(x+2)